Alloyed heterostructures of CdSexS1–x nanoplatelets with highly tunable optical gain performance - Kelestemur, Yusuf (2021)
Here, we designed and synthesized alloyed heterostructures of CdSe S nanoplatelets (NPLs) using CdS coating in the lateral and vertical directions for the achievement of highly tunable optical gain performance. By using homogeneously alloyed CdSe S core NPLs as a seed, we prepared CdSe S /CdS core/crown NPLs, where CdS crown region is extended only in the lateral direction. With the sidewall passivation around inner CdSe S cores, we achieved enhanced photoluminescence quantum yield (PL-QY) (reaching 60%), together with increased absorption cross-section and improved stability without changing the emission spectrum of CdSe S alloyed core NPLs. In addition, we further extended the spectral tunability of these solution-processed NPLs with the synthesis of CdSe S /CdS core/shell NPLs. Depending on the sulfur composition of the CdSe S core and thickness of the CdS shell, CdSe S /CdS core/shell NPLs possessed highly tunable emission characteristics within the spectral range of 560-650 nm. Finally, we studied the optical gain performances of different heterostructures of CdSe S alloyed NPLs offering great advantages, including reduced reabsorption and spectrally tunable optical gain range. Despite their decreased PL-QY and reduced absorption cross-section upon increasing the sulfur composition, CdSe S based NPLs exhibit highly tunable amplified spontaneous emission performance together with low gain thresholds down to ∼53 μJ/cm2 .